Profil berpikir reflektif siswa dalam menyelesaikan soal tipe-tipe perkalian ditinjau dari perbedaan kemampuan matematika dan gender - Agustina Sukarno Putri; Helti Lygia Mampouw (Math Didactic: Jurnal Pendidikan Matematika, 2018)
Reflective thinking is concerned with the ability to review, monitor, and monitor the solution process when troubleshooting. This qualitative research aims to describe the reflective thinking ability of junior high school student in solving the problem of scalar multiplication type, array multiplication and combinatorial multiplication based on different ability of math and gender. The subjects consisted of 3 male students and 3 female students of grade VII SMP who each had high, medium and low math skills. The result show taht male and female students with high math skills have reflective thinking skills for all type of questions. Student with math skills are capable of reflective thinking for scalar multiplication types and reflective enough in combinatorial multiplication types. Male students with low math skills tend to be less reflective on all types of questions and female students have reflective thinking skills on all types have reflective. It was also ound that male students tend to be able to use ilustrations, for example with pictures whereas female students tend to solve problems on a regular basis for example by writing known, questioned, and answered. These results are expected to help teachers and researchers to understand the level of reflective thinking of students on the type of multiplication in terms of differences in mathematical ability and gender.